Productivity and Carbon Utilization of Three Green Microalgae Strains with High Biotechnological Potential Cultivated in Flat-Panel Photobioreactors - Gabrielyan, David A.; Sinetova, Maria A.; Savinykh, Grigoriy A.; Zadneprovskaya, Elena V.; Goncharova, Maria A.; Markelova, Alexandra G.; Gabrielian, Alexander K.; Gabel, Boris V.; Lobus, Nikolay V. (Phycology, 2025)
Microalgae biotechnology is increasingly applied across diverse fields, from food and medicine to energy and environmental protection, with strain selection being crucial for both target product accumulation and scalability potential. In this study, we for the first time assess the scalability of two new promising green microalgae strains, Neochlorella semenenkoi IPPAS C-1210 and Desmodesmus armatus ARC-06, in 5-L flat-panel photobioreactors. The growth characteristics of each culture, along with their biochemical composition and CO2 utilization efficiency, were examined and compared to the well-studied model strain Chlorella sorokiniana IPPAS C-1. While C-1 achieved the highest biomass concentration (7.1 ± 0.4 g DW L−1 by day 8) and demonstrated superior specific productivity (1.5 ± 0.1 g DW L−1 d−1) and CO2 utilization efficiency (average 25.4%, peaking at 34% on day 3), ARC-06 accumulated the highest starch content (51% of DW), twice that of C-1. Strain C-1210 showed intermediate performance, reaching 6.8 ± 0.8 g DW L−1 biomass with a CUE of 22.7%, whereas ARC-06 had the lowest CUE (12.8%). These results, combined with proposed cultivation optimization strategies, provide a foundation for scaling up N. semenenkoi and D. armatus production in industrial flat-panel PBR systems.